Clostridium butyricum extracellular vesicles remodel the transcriptional network of pyroptosis-related genes in LPS-stimulated macrophages - Zhang, Qingyu; He, Kailun; Aazmi, Mohd Shafiq; Yahya, Mohd Fakharul Zaman Raja (Frontiers in Immunology, 2026)
BackgroundExtracellular vesicles (EVs) of probiotics are an important pathway for probiotics to exert probiotic effects. EVs of Clostridium butyricum (C. butyricum) has great potential in immunotherapy. The aim of this study is to investigate the regulatory effect of C. butyricum EVs on the pyroptosis-related gene network in LPS-stimulated macrophages and explore its potential molecular mechanisms.MethodsDifferential centrifugation was used to isolate C. butyricum EVs, and EVs were characterized by transmission electron microscopy, NTA, and ZETA potential. PI staining was employed to confirm the stimulatory effect of LPS on RAW264.7 cells. Transcriptome sequencing and qPCR were performed to validate the regulatory effects of EVs on pyroptosis-related genes (PRGs) in LPS-stimulated RAW264.7 cells.ResultsC. butyricum EVs exhibited a bilayer membrane structure with a median particle size of 144.4 ± 85.7 nm and a ZETA potential of -37.56 ± 1.08 mV. PI staining showed that LPS induced cell death in RAW264.7 macrophages, while EV treatment significantly affected the expression of pyroptosis-related genes IL-18 and IL-33 (q < 0.05). Transcriptome analysis revealed that C. butyricum EVs induce inflammation and cytokine secretion in RAW264.7 macrophages through the JAK-STAT signaling pathway and Cytokine receptor interaction. EVs pretreatment (10/20 μg/mL) regulated the expression of 14 PRGs in a concentration-related manner, including significant upregulation of IL-6 and P2rx7 (q < 0.01) and inhibition of ZBP1 and Tnf (q < 0.05). The gene interaction network showed a positive correlation (r=0.82) between IL-6 and P2rx7, and a negative correlation (r=-0.75) between ZBP1 and P2rx7.ConclusionC. butyricum EVs remodel the pyroptosis-related regulatory network by modulating key genes such as IL-6, P2rx7, and ZBP1, suggesting their potential role in fine-tuning LPS-induced inflammatory responses in macrophages.